Carbon Quantum Dot-Catalyzed, Highly Efficient Miniemulsion Atom Transfer Radical Polymerization Induced by Visible Light - Qiao, Xiaoguang; Qiao, Liang; Zhou, Mengjie; Zhang, Xi; Shi, Ge; He, Yanjie; Bourgeat-Lami, Elodie; Pang, Xinchang (ACS macro letters, 2022)
Owing to the benefits of using natural or artificial light sources as a stimulus, photoinduced reversible-deactivation radical polymerization (photoRDRP) techniques have been recognized to be a powerful “green” platform for the preparation of well-defined polymers. However, the development of highly efficient visible light-induced photoRDRP processes in aqueous dispersed media remains a challenge due to light scattering and refraction by monomer droplets or colloidal particles. In this work, an efficient green photocatalyst, carbon quantum dots (CQDs), was introduced to visible light-mediated miniemulsion atom transfer radical polymerization (ATRP), leading to highly efficient polymerizations with reaction rates (>80% monomer conversion within 1 h) much higher than in previous studies. This heterogeneous photocatalytic system is presumed to involve three catalytic cycles in (i) the aqueous phase, (ii) the oil–water interface, and (iii) the monomer droplets. The effect of different polymerization parameters on the polymerization reaction was investigated, including the amounts of surfactant and CQDs, CuBr2 dosage, and solid content. Excellent temporal control of the polymerization was illustrated by “ON/OFF” polymerizations, and natural sunlight was also used as an energy source. This novel CQDs-catalyzed miniemulsion photoATRP process may be easily extended to other aqueous dispersion RDRP systems. As an extension of our previous work (J. Am. Chem. Soc. 2022, 144 (22), 9817–9826) we also developed a “one-pot” method for the rapid preparation of heterogeneous hydrogels.